Heparan sulfates from bat and human lung and their binding to the spike protein of SARS-CoV-2 virus. (15th May 2021) - Yan, Lufeng; Song, Yuefan; Xia, Ke; He, Peng; Zhang, Fuming; Chen, Shiguo; Pouliot, Robert; Weiss, Daniel J.; Tandon, Ritesh; Bates, John T.; Ederer, Dallas R.; Mitra, Dipanwita; et al.
Highlights: Heparan sulfate (HS) is a co-receptor for SARS-CoV-2. SARS-CoV-2 is a zoonotic respiratory virus. The primary host of SARS-CoV-2 is bats. Bat and human lung tissue HS have different structures. Human lung HS binds tighter to SARS-CoV-2 spike protein. Abstract: Severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) has resulted in a pandemic and continues to spread at an unprecedented rate around the world. Although a vaccine has recently been approved, there are currently few effective therapeutics to fight its associated disease in humans, COVID-19. SARS-CoV-2 and the related severe acute respiratory syndrome (SARS-CoV-1), and Middle East respiratory syndrome (MERS-CoV) result from zoonotic respiratory viruses that have bats as the primary host and an as yet unknown secondary host. While each of these viruses has different protein-based cell-surface receptors, each rely on the glycosaminoglycan, heparan sulfate as a co-receptor. In this study we compare, for the first time, differences and similarities in the structure of heparan sulfate in human and bat lungs. Furthermore, we show that the spike glycoprotein of COVID-19 binds 3.5 times stronger to human lung heparan sulfate than bat lung heparan sulfate.